2022
DOI: 10.1111/apt.17088
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of viral hepatocellular carcinoma but not non‐viral hepatocellular carcinoma from 2000 to 2020: A multi‐centre cohort study of 6007 patients from high‐volume academic centres in Japan

Abstract: Summary Background While surveillance improves the early detection of hepatocellular carcinoma (HCC), it is unclear whether this has improved prognosis in clinical practice. Aims To investigate the characteristics and prognoses of patients with viral versus non‐viral HCC over the previous two decades in Japan, while HCC surveillance has been active. Methods This multi‐centre study enrolled 6007 patients initially diagnosed with HCC between 2000 and 2020 at seven high‐volume academic centres. Patients were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In our cohort, 53.5% of the patients in the nonviral HCC group did not have liver cirrhosis. Despite the lower annual incidence in the NAFLD-related (HCC group (0.44 per 1000 person-years)), several countries, including nations in Europe and Asia, have shown increased prevalence rates of nonviral HCC and its association with NAFLD 10 , 16 , 17 . There was strong evidence supporting abdominal ultrasound screening to reduce HCC mortality 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 53.5% of the patients in the nonviral HCC group did not have liver cirrhosis. Despite the lower annual incidence in the NAFLD-related (HCC group (0.44 per 1000 person-years)), several countries, including nations in Europe and Asia, have shown increased prevalence rates of nonviral HCC and its association with NAFLD 10 , 16 , 17 . There was strong evidence supporting abdominal ultrasound screening to reduce HCC mortality 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Manikat and Nguyen 1 in our article comparing survival improvement in patients with hepatocellular carcinoma (HCC) caused by viral versus non-viral liver diseases. 2 We envision that the lack of improvement in patients with non-viral HCC may be a global phenomenon.…”
Section: Editorsmentioning
confidence: 99%
“…
We would like to congratulate the authors Toyoda et al on their very important study broadly covering Japan. 1 The article highlights the rising incidence of nonviral hepatocellular carcinoma (HCC), an area of increasing medical urgency. The study also found significant disparities in the survival of nonviral versus viral HCC patients.
…”
mentioning
confidence: 99%